Understanding the genetic basis of resistance to maydis leaf blight and maturity-related traits in corn - Kumar, Bhupender; Pushpendra,; Kumar, Santosh; Kumar, Pardeep; Singh, Rakhi; Yankanchi, Shrikant; Sarkar, Debjyoti; Nath, Chhavi; Jat, Bahadur Singh; Bagaria, Pravin Kumar; Aggarwal, Sumit Kumar; Piyal, Prahlad; et al. (Frontiers in Plant Science, 2025)
Maize is one of the most versatile and commercially produced crops used for food, feed, fodder, ethanol, oil, and industrial raw materials. Maize is affected by various diseases, but among these, maydis leaf blight (MLB) is one of the most serious diseases. The disease is caused by Cochliobolus heterostrophus and is responsible for yield losses up to 40%. When developing cultivars for a specific ecology, days to flowering and maturity are important breeding traits to consider. Thus, understanding the genetic basis of MLB resistance, specifically the “O” race of the pathogen, and maturity-related traits is crucial to develop climate-resilient maize hybrids. This study aimed to determine the gene actions and their interactions for MLB resistance and maturity-related traits using a six-parameter model (P1, P2, F1, BC1P1, BC1P2, and F2). Five experimental crosses were attended using resistant (R) (CML269-1 and P72c1Xbrasil1177-2) and susceptible (S) (HKIPC4B and ESM113) lines in R×S (1), S×R (2), R×R (1), and S×S (1) combinations. The susceptible lines belonged to the early (HKIPC4B) and medium (ESM113) maturity groups, while the resistant lines belonged to the medium (CML269-1) and late (P72c1Xbrasil1177-2) maturity groups. These six genetic populations were screened under artificially created epiphytotic conditions at a hot-spot site. In the analysis, MLB resistance showed a dominance genetic effect with significant (P<0.01) additive × additive interactions. Maturity-related traits showed significant dominance genetic effects (P< 0.01), with dominance × dominance interactions, suggesting the suitability of hybrid breeding for these traits. The estimated genes responsible for MLB resistance ranged from 0.002 to 5.78 per cross. In MLB resistance, broad and narrow-sense heritability were found to be 91.9% and 84.3%, respectively, which indicated the possibility of genetic improvement through selection. Disease response and maturity-related traits were negatively correlated, suggesting that long-duration genotypes are more resistant to disease than short-duration. The detailed understating of gene actions can aid in designing breeding strategies to develop resistant cultivars with the required duration for various stress-prone ecologies.